Možnosti uporabe potresne izolacije iz elastomernih ležišč za varstvo kulturne dediščine - Petrovčič, Simon (Urbani izziv, 2009)
This article briefly presents the applicability of base isolation made of elastomeric isolators for the protection of heritage architecture. The first part of the article gives an illustrative overview on the use of base isolation throughout the world, together with an analysis of guidelines for the protection and management of places of heritage architecture. The guidelines which are given through international agreements and resolutions on the conservation of monuments have to be considered when designing the base isolation of existing monuments. Generally, interventions into such structures should be minimal or visible as little as possible and should minimally affect the aesthetics and functionality of the object. In the second part of the article the general and some special requirements for base isolation design with elastomeric isolators are presented. The influence of the slenderness of the structure is analysed in more detail. The analysis is based on the corresponding rocking prevention criterion, upon the condition that the isolators cannot bear any tensile forces. The article concludes with a presentation of the maximum height-to-width ratios for objects that can be mounted on isolators, fulfilling the given rocking prevention criterion for different soil conditions. The maximum aspect ratios have also been determinedby considering 5 appropriately scaled ground motions from the 1998 Posočje earthquake.
Keywords: arhitekturna dediščina; cultural heritage; izolacija; kulturna dediščina; obnova; potresna varnost; visokoelastični materiali